Does accountant CFO matter to auditor? - Gabriella Handoyo; Yani Permatasari; Nadia Anridho; Khairul Anuar Kamarudin; Agnes Aurora Ngelo (Jurnal Akuntansi dan Auditing Indonesia, 2023)
Chief Financial Officer (CFO) is a chief executive whose responsibilities are related to accounting and audit work. However, there is a downward trend in hiring CFOs with an accounting background. Therefore, we aim to study the relationship between accountant CFO and audit outcomes. This paper use samples of non-financial firms listed on the Indonesia Exchange Stock (IDX) from 2010 to 2018 and using OLS with a cluster by the firm in Stata 17.0 to analyze the relationship between accountant CFO and audit outcomes. We document that accountant CFOs tend to appoint Big4 accounting firms because they demand a higher audit quality. Furthermore, the results suggest that accountant CFOs are more likely to have a higher audit fee, a higher audit quality, and a shorter audit report lag. This finding shows that the accountant CFO can be related to the audit outcomes and this shows how auditors value the accountant CFOs. We expect this paper contributes to enrich the literature on accountant CFO and helps firms in hiring their CFO.